An Study Of The Effect Of Classroom Collaboration On The Attainments Of Students At The Secondary School Level - Malik Amer Atta (Elementary Education Online, 2023)
The goal of the study was to compare the effects of student cooperation in the classroom on secondary school student’s academic achievement. Finding the academic achievement of students who collaborated in class and discovering the academic achievement of students who did not collaborate in class were the study’s key goals. All secondary school pupils are included in the population for the research. Using a random sampling approach, the sample was chosen. In this investigation, two tools were employed. To first assess how the experimental group and control group performed, a pre-test was employed. The performance of the experimental group and control group was evaluated following the experiment using a post-test. This study’s methodology involved two equal groups. A cooperation facility was made available to the experimental group, but not to the control group. The pupils were given a post-test following fifteen days of instruction. Tables were created with the results of both exams. Data analysis was done using the t-test statistic. This indicates that the accomplishment of the control and experimental groups differs. The test group received classroom instruction. Collaboration outperformed the control group substantially. Therefore, the null hypothesis was rejected since there was evidence of an active cooperation pattern in the experimental group as opposed to the control group, which did not have access to a collaboration facility in the classroom. Teachers should indulge and engage themselves, the study suggests, and they should deviate from established routines and involve themselves and their students in the teaching-learning process.